Pelaksanaan Hukum Waris Masyarakat Desa Susuk Kecamatan Tiga Nderket Berdasarkan Hukum Adat Karo dan Hukum Positif - Tri Nastiya; Wahdina Aulia; Nurhaliza Nurhaliza; Izzatunnada Izzatunnada (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
One of the conditions for the occurrence of inheritance is because there are heirs and heirs. The closest heir to the right to inherit property is a child. The child is the fruit of love from a marriage. In the Karo tribe, marriage is an important way to continue the descendants of the clan brought by sons. So do not be surprised if men are slightly more privileged than women. The same applies to inheritance. Men are entitled to all inheritance while women are not entitled to become heirs but are still given property in the form of an indefinite gift. The existence of customary law in Indonesia is stated in Article 18B paragraph 2 of the 1945 Constitution that the state recognizes and respects the provisions of customary law. However, as time passed, the Karo customary law community became more and more open minded to stimuli outside of customary provisions. Starting from transmigration to several areas, cross-breeding between tribes and the entry of outsiders from the Karo tribe into the area made cultural acculturation. The position of customary law is under the codified positive law of Indonesia. This happens so that the provisions of customary law do not deviate from the goals and principles of the Indonesian nation. One of them with the Supreme Court Decision No. 179K/Sip/1961 as a form of equal rights efforts between male and female heirs in the Karo community. Therefore, this research was conducted with a juridical, empirical and sociological system in obtaining data. Are the people of Susuk Village, Kec. Three Nderket Kab. Karo still maintains customary law or collaborates with positive Indonesian law regarding the inheritance law.